Jouer le jeu ? Les Palestiniens du Liban, entre marginalisation sociale et « rhétorique de l’officiel » - Nicolas Dot-Pouillard (Revue des Mondes Musulmans et de la Méditerranée)
Since 2006 and the reopening of the representation of the Palestinian Liberation Organization (PLO) in Beirut and the creation of the Lebanese-Palestinian Dialogue Committee (LPDC) in 2006, Palestinians and Lebanese developed a “rhetoric of the official,” where they would negotiate as equals the living conditions of the Palestinians refugees. Lebanese recognition of “a right to have rights”, does not imply an immediate granting of such rights. Palestinian political organizations play along however, so that recognition of a “rhetoric of the official” is evidence that the Lebanese-Palestinian dialogue works. People excluded from the dialogue—youth movements, neighborhood committees, Salafists—denounce the terms of the dialogue but do not rule out their future participation. The “rhetoric of the official” postulates a successful Lebanese-Palestinian dialogue. The real question here is whether it has a performative impact or remains solely a political fiction.